Status Kesehatan dan Uji Spesies Indikator Biologi Ekosistem Mangrove Teluk Yotefa Jayapura - John Dominggus Kalor; Lisiard Dimara; Ottouw G. Swabra; Kalvin Paiki (Fakultas Biologi | Universitas Jenderal Soedirman, 2018)
This research was conducted to test the mangrove crab of Sesarmidae family as bio-indicator to assess health status of mangrove ecosystem in Youtefa Bay of Jayapura. Conducted since March-August 2017. Conducted in 3 stations namely St. Enggros, St.Tobati, and St. Nafri. Using the quadratic transect method (1x 1 m) and the quadratic transect (10 x 10 m). Data were analyzed using index of diversity, dominance, evenness, abundance, density, simple linear regression and test criteria of indicator species. The result of the research found the level of mangrove diversity in Enggros Station with the value of index 1.9 then Tobati and Nafri Station of 1, 4 with abundant diversity level. The density of mangroves in the three stations is obtained by Enggors: 1455.6 trees / Ha, Naftri: 1477.8 trees / Ha, and Tobati 1033,5 trees / ha with moderate density categories and good ecosystem health conditions. The biological criteria indicator test shows that the Sesarmidae crab meets the six criteria of the indicator species, so that it can be designated as a species indicator of the health status of the ecosystem.